(untitled) (Bioscience Journal, 2020)
Crambe (Crambe abyssinica H.), a promising species in the production of biodiesel, has low planting cost, high oil content and easy extraction, besides being an alternative for the crop rotation system. The objective of this study was to evaluate the effects of nitrogen fertilization and line spacing on the production components and yield of the crambe crop under semi-arid conditions. The study was conducted under field conditions in the experimental area of the National Semi-Arid Institute-INSA, located in the city of Campina Grande-PB. The experimental design was a randomized complete block design in 4 x 2 factorial scheme, consisting of four nitrogen doses (30, 60, 90, 120 kg ha-1) with two spacings between planting lines (0.20 and 0.40 meters) with three replications, totaling 24 experimental plots. The evaluated parameters were: number of siliques per plant, dry weight of shoots, number of branches (primary and secondary), primary stem length, number of siliques per stem, mass of 1000 grains and productivity. The data were submitted to analysis of variance, in which the nitrogen doses (quantitative factor) were compared by regression analysis. The different spacings were compared by means of a t-test at the 0.05 probability level by using statistical software SISVAR version 5.2. Nitrogen fertilization at 0.40 m spacing between the planting lines led to the best results for the production components, and the highest productivity was obtained at 0.20 m spacing of with nitrogen fertilization of 120 kg ha-1.